2018
DOI: 10.1590/1806-93042018000200007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy and early development of overweight and growth deficit in children: an analysis of survival

Abstract: Objectives: to evaluate the association between smoking during pregnancy and nutritional status. Methods: cohort study with a sample of 460 children in the baseline. The children were assessed four times, being measured for weight and length to be converted in indexes length forage (L/A) and body mass index forage (BMI/A) in Z-score. The time until occurrence of growth deficit and overweight was calculated in days and compared to maternal smoking during pregnancy. To assess the association between smoking dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
1
0
3
Order By: Relevance
“…Other studies have shown likely results: EBF for less than four months is associated with lower consumption of fruits and vegetables and higher consumption of ultra-processed foods [39]. It can be seen that feeding introduction at the right time, in a non-early stage, is associated with EBF in the rst month of life [40].…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have shown likely results: EBF for less than four months is associated with lower consumption of fruits and vegetables and higher consumption of ultra-processed foods [39]. It can be seen that feeding introduction at the right time, in a non-early stage, is associated with EBF in the rst month of life [40].…”
Section: Discussionmentioning
confidence: 91%
“…O estudo conduzido por Fonseca et al (2018) para verificar os efeitos do tabagismo na gestação sobre o excesso de peso e déficit de crescimento em crianças nos primeiros seis meses de vida, precisou que as crianças expostas ao fumo na gestação, desenvolveram excesso de peso primeiro que as não expostas. De igual modo, quando verificado acerca do desenvolvimento do déficit de comprimento nas crianças até o sexto mês de vida, o fumo materno durante a gestação se mostrou uma causa independente também para esta variável.…”
Section: Discussionunclassified
“…Por isso, a análise detalhada com medidas repetidas nesse período, permite avaliar de forma mais precisa quando as mudanças no estado nutricional infantil começam a ocorrer. Poucos estudos dispõem de medidas repetidas no primeiro ano de vida (FONSECA et al, 2018).…”
Section: Justificativaunclassified
“…Similar ao presente estudo, outras pesquisas também não encontraram associação entre tabagismo materno na gestação e as médias de z-escore de IMC/I ao longo do primeiro ano de vida. A associação do fumo materno durante a gestação e as médias de z-escore de IMC/I da criança tem sido referida em alguns estudos, porém a associação mais robusta estatisticamente significante ocorre apenas no final do primeiro ano de vida ou em períodos posteriores da primeira infância (FONSECA et al, 2018).…”
Section: Variáveis De Interesse Do Estudounclassified